Common adverse events following immunization with the COVID-19 comirnaty vaccine (Pfizer-BioNTech) among adult population in Hanoi, Vietnam, 2021 - Le, Xuan Thi Thanh; Hoang, Quan Long; Ta, Nhung Thi Kim; Pham, Quan Thi; Nguyen, Thao Thanh; Phan, Huong Thi Mai; Nguyen, Thanh Van; Le, Ha Thi Thanh; Nguyen, Nam Thuy; Hoang, Linh Dieu; Luong, Phuong Thi Huyen; An, Lien Hong; et al. (Frontiers in Tropical Diseases, 2022)
Rationale: To prevent and control the COVID-19 pandemic, the biggest immunization campaign in history had been deployed all around the globe. However, many people rejected being vaccinated because of the concern about the adverse events following immunization (AEFI). Objectives: To prevent vaccine hesitancy, this study focused on finding the common adverse events following immunization with the COVID-19 COMIRNATY vaccine (Pfizer-BioNTech) among people aged 18 and above and related factors in Hanoi, Vietnam. Methods: A cross-sectional study was carried out to collect participants’ data and AEFI after being vaccinated at Hanoi Medical University, Vietnam in 2021. Random sampling was conducted to select 820 who received both doses of Pfizer vaccine in August and September 2021. Logistic regression was used to analyze correlated factors of AEFI. Results: The proportion of AEFI after the first dose, second dose, and both doses of Pfizer vaccine were 24.4%, 64.2%, and 18.5%, respectively. AEFIs mostly appeared within 1 day and lasted for 1 or 2 days. The AEFIs were more common in females (Pfizer: OR=1.7; 95%CI=1.25-2.29) and younger age groups (Pfizer: OR=1.9; 95%CI=1.37-2.58). History of allergic, allergic diseases, chronic diseases and occupations were not statistically significant with AEFI. Conclusion: Our findings showed that the COVID-19 COMIRNATY vaccine is safe to be injected. Gender and age group are important factors that influence AEFI.